2006
DOI: 10.1074/jbc.m600294200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-specific Differential Induction of the Human γ-Fibrinogen Promoter by Interleukin-6

Abstract: During an acute phase response, interleukin-6 (IL-6) and glucocorticoids up-regulate expression of the three fibrinogen (FBG) genes (fga, fgb, and fgg) in liver and lung epithelium; however, little constitutive lung expression occurs. Recently, we showed that the magnitude of Stat3 binding to three IL-6 motifs on the human ␥FBG promoter correlates negatively with their functional activity in hepatocytes, although these cis-elements are critical for promoter activity. We determined the role of IL-6-receptor-gp1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…The interaction of glucocorticoids with STAT3 have been described earlier for the regulation of genes like fibrinogen and alpha 2 macroglobulin (Duan and Simpson-Haidaris, 2006;Lerner et al, 2003;Takeda et al, 1998). In all these cases GCs do have little activity on their own but they operate synergistically with IL-6 induced STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of glucocorticoids with STAT3 have been described earlier for the regulation of genes like fibrinogen and alpha 2 macroglobulin (Duan and Simpson-Haidaris, 2006;Lerner et al, 2003;Takeda et al, 1998). In all these cases GCs do have little activity on their own but they operate synergistically with IL-6 induced STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that lung, prostate and breast cancer epithelial cells synthesize and secrete Fg that enhances FGF-2-mediated cell proliferation, assembles into extracellular matrices and binds to cancer cell surfaces. 2,14,[32][33][34][35][36][37] In addition, others have demonstrated Fg production in adenocarcinoma cell lines of cervical 15 and intestinal 16 origin. Recent expression array profiling studies have confirmed that the Fg genes are expressed in breast 17 and lung carcinomas 18,19 isolated from patients.…”
Section: Discussionmentioning
confidence: 99%
“…The negative control peptide corresponding to fibrinopeptide A induced minimal %FITC-Dextran Flux compared with Fg or peptide b 15-42 (#p < 0.0001); however, the 13% relative fluorescence was significant (-p 5 0.001) compared with basal levels that were 1% of intact Fg-induced permeability. Peptides missing b 15-17 residues (b [18][19][20][21][22][23][24][25][26][27][28][29][30][31] or b [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] ) or truncated at the C-terminus (b [15][16][17][18][19][20][21][22][23][24][25][26][27] (Fig. 2c).…”
Section: Fg-induced Ec Permeability Involves Fg-b 15-42 Sequences Andmentioning
confidence: 99%
See 1 more Smart Citation
“…One important mechanism involving the (IL-1-mediated) activation of IL-6 that in turn induces fibrinogen synthesis by hepatocytes [484][485][486] and other cells 482,[487][488][489][490] is especially pertinent. IL-6 is also involved in iron (dys)regulation, in particular by its ability to induce hepcidin biosynthesis (e.g.…”
Section: Cytokines Linking Inflammation Hypercoagulability and Hypofmentioning
confidence: 99%